Biophysical screening methods for extracellular domain peptide receptors, application to natriuretic peptide receptor C ligands. (10th October 2018) - Conole, Daniel; Myers, Samuel H.; Mota, Filipa; Hobbs, Adrian J.; Selwood, David L.
Abstract: Endothelium‐derived C‐type natriuretic peptide possesses cytoprotective and anti‐atherogenic functions that regulate vascular homeostasis. The vasoprotective effects of C‐type natriuretic peptide are somewhat mediated by the natriuretic peptide receptor C, suggesting that this receptor represents a novel therapeutic target for the treatment of cardiovascular diseases. In order to facilitate our drug discovery efforts, we have optimized an array of biophysical methods including surface plasmon resonance, fluorescence polarization and thermal shift assays to aid in the design, assessment and characterization of small molecule agonist interactions with natriuretic peptide receptors. Assay conditions are investigated to explore the feasibility and dynamic range of each method, and peptide‐based agonists and antagonists are used as controls to validate these conditions. Once established, each technique was compared and contrasted with respect to their drug discovery utility. We foresee that such techniques will facilitate the discovery and development of potential therapeutic agents for NPR‐C and other large extracellular domain membrane receptors. Abstract : C‐type natriuretic peptide and its cognate receptor, natriuretic peptide receptor C, represent a novel therapeutic target for the treatment of cardiovascular diseases. To facilitate our drug discovery efforts, we have optimized an array of biophysical methods including surface plasmon resonance, fluorescence polarization and thermal shift assays to aid in the design, assessment and characterization of small molecule agonist interactions with natriuretic peptide receptors.